The body my mother gave me - Riedl, Morgan, author; Thompson, Deborah, advisor; Sloane, Sarah, committee member; Kodrich, Kris, committee member (Colorado State University. Libraries, 2017)
This collection of personal essays investigates the theme of identity, specifically identity in flux, how and why it changes, paying particular attention to the influence of relationships. Mostly memoir, these essays experiment with form and structure, often in the genre of the lyric essay, using braids, collage, and a hybrid style. The intention of this narrative choice is to allow for form and structure to be in conversation with the construction of meaning. This collection is organized around the body and its perception, so the individual essays study body parts responsible for sensing or interacting with the world to understand the self as separate from others but also its connection with others, with a keen eye on gender. The collection is most interested in the question and exploration of the one responsible for creating this self, physically and metaphorically. Thus, much of this body of work concentrates, directly and indirectly, on my relationship with my mother. This collection takes a special interest in the complication that, while the body and mind are connected and inseparable, they are not always congruent, much like relationships, both personal and with society as a whole. A smaller vein running throughout is the influence of both time and space—however unknowable and uncontrollable—in the creation and understanding of self in the context of something greater.